2014
DOI: 10.1590/s0102-71822014000200011
|View full text |Cite
|
Sign up to set email alerts
|

Representações sociais de caminhoneiros de rota curta sobre HIV/AIDS

Abstract: Neste estudo qualitativo objetivou-se analisar representações sociais de caminhoneiros de rota curta sobre a AIDS, transmissão do HIV e prevenção da AIDS. Envolveu 19 caminhoneiros de rota curta, de uma associação em Vitória da Conquista-BA. A produção dos dados foi por intermédio de entrevista semiestruturada e por análise de conteúdo temática, sendo identificadas três categorias êmicas. Os resultados mostraram que as representações sociais da AIDS estavam ancoradas nos constructos: "doença ruim", "doença per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
16
0
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 24 publications
3
16
0
7
Order By: Relevance
“…The low incidence of comorbidities was an expected outcome in this study, as most participants did not use drugs, had not stopped ART, and had not been hospitalized due to HIV complications. The absence of comorbidities predictor was related to a decrease in the stigmatization mean, since in addition to a lack of pathological signs and symptoms being a good health indicator, it helped hide the diagnosis by maintaining the confidentiality of HIV infection, preserving people from discriminatory situations (18,20) . In a study carried out in Mozambique, women who had signs and symptoms suggesting AIDS such as weight loss and fever, in addition to feelings of hopelessness in the face of the "bad", "incurable" disease that leads to death (20) , also felt guilty and devalued because they were labeled in the community and strongly stigmatized for presenting signs that exposed their condition of seropositivity (21) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The low incidence of comorbidities was an expected outcome in this study, as most participants did not use drugs, had not stopped ART, and had not been hospitalized due to HIV complications. The absence of comorbidities predictor was related to a decrease in the stigmatization mean, since in addition to a lack of pathological signs and symptoms being a good health indicator, it helped hide the diagnosis by maintaining the confidentiality of HIV infection, preserving people from discriminatory situations (18,20) . In a study carried out in Mozambique, women who had signs and symptoms suggesting AIDS such as weight loss and fever, in addition to feelings of hopelessness in the face of the "bad", "incurable" disease that leads to death (20) , also felt guilty and devalued because they were labeled in the community and strongly stigmatized for presenting signs that exposed their condition of seropositivity (21) .…”
Section: Discussionmentioning
confidence: 99%
“…The absence of comorbidities predictor was related to a decrease in the stigmatization mean, since in addition to a lack of pathological signs and symptoms being a good health indicator, it helped hide the diagnosis by maintaining the confidentiality of HIV infection, preserving people from discriminatory situations (18,20) . In a study carried out in Mozambique, women who had signs and symptoms suggesting AIDS such as weight loss and fever, in addition to feelings of hopelessness in the face of the "bad", "incurable" disease that leads to death (20) , also felt guilty and devalued because they were labeled in the community and strongly stigmatized for presenting signs that exposed their condition of seropositivity (21) . Thus, avoiding illness and correctly adhering to ART does not only depend on information and on the individual's posture, but also on many structural factors which are linked to the stigma and perceptions of the disease, and affect individuals regardless of their will (4,14) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 The results showed that the social representations of AIDS were anchored in: "bad disease", "dangerous disease", "incurable illness" and "disease that kills". HIV transmission was related to unprotected sex with sex professionals, gays and contact with contaminated blood; AIDS prevention was represented by the use of condoms in extramarital relationships and wife fidelity.…”
mentioning
confidence: 99%
“…Research about the social representations of truck drivers about HIV/AIDS articulates the disease with negative aspects, being translated as dangerous, incurable and lethal, denoting the knowledge of the beginning of the epidemic. 24 From this perspective, it is shown the image dimensions and attitude linked to representation object, characterized by HIV/AIDS. It is worth mentioning that fear is a feeling that occurs due to anxiety facing danger or a real or imaginary threat.…”
mentioning
confidence: 99%